2019
DOI: 10.1088/1741-4326/ab266d
|View full text |Cite
|
Sign up to set email alerts
|

Self-driven current generation in turbulent fusion plasmas

Abstract: Global gyrokinetic simulations with self-consistent coupling of neoclassical and turbulent dynamics show that turbulence can significantly affect plasma self-driven mean current generation in tokamaks. The current amplitude, profile and associated phase space structures can all be modified. Turbulence can significantly reduce the current generation in the collisionless regime, generate current profile corrugation near the rational magnetic surface and nonlocally drive current in the linearly stable region—all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 32 publications
(48 reference statements)
1
23
1
Order By: Relevance
“…5 The current driven by turbulence has been discussed in detail using the analytical and numerical approaches. 3,4,[6][7][8][9][10] It has been shown by S. -I. Itoh and K. Itoh firstly with a slab model. 6 Driftwave fluctuations drive a net current when k is finite, where k is the averaged parallel wave number over the spectrum .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…5 The current driven by turbulence has been discussed in detail using the analytical and numerical approaches. 3,4,[6][7][8][9][10] It has been shown by S. -I. Itoh and K. Itoh firstly with a slab model. 6 Driftwave fluctuations drive a net current when k is finite, where k is the averaged parallel wave number over the spectrum .…”
Section: Introductionmentioning
confidence: 93%
“…The spontaneous variation of electron momentum provides a current source which corrugates the current density profile and has significant impacts on the generation of the plasma self-driven mean current. 3,4 The current induced by turbulence affects the MHD instabilities which can provide a way to study the interaction between the turbulence and the MHD instabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades since the invention of the tokamak, various external or self-generated current drive mechanisms have been developed for steady-state operations, such as radio frequency-driven, neutral beam injection (NBI)-driven, and bootstrap current. Recently, it was found that micro-instabilities can also generate or modify the plasma current 1 4 , which could probably explain an anomaly in the current profile found in experiments such as in the hybrid operation scenario 5 . The self-generated current drive mechanisms have been predicted in theories 1 , 2 , 4 , 6 , then discovered in experiments 7 9 and they were found to be consistent with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that micro-instabilities can also generate or modify the plasma current 1 4 , which could probably explain an anomaly in the current profile found in experiments such as in the hybrid operation scenario 5 . The self-generated current drive mechanisms have been predicted in theories 1 , 2 , 4 , 6 , then discovered in experiments 7 9 and they were found to be consistent with each other.…”
Section: Introductionmentioning
confidence: 99%